Security of tenure in employment: an employees precious 'property' - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2010)
Security of tenure in employment is an essential component of a workers sense of identity, self worth and emotional well being, amongst other things. Dismissal from employment would have financial repercussions and psychological effects on the worker. Recently, the Minister of Human Resources and Manpower announced the proposed amendments to the Industrial Relations Act 1967. 'The amendment is deliberately designed to empower employers to employ workers on fixed term contract for as long as they please'. The above proposal, if passed, would remove security of tenure in employment to workers in the private sectors. In relation to the above, the importance of security of tenure in employment is emphasised in this article. It is argued that while attempting to attract foreign direct investments into the country, which is important for financial and human capitals to the economy, workers security of tenure in employment should not be compromised. This is primarily so because labour is not and should never be construed as a commodity. The capitalists perceive the right to appoint and let off their commodities (the employees) as and when they pelase, as a system seen to operate under the doctrine of 'at-will' employment in the United States or at common law, under the doctrine of hire and fire. The workers are being subject to exploitation as they are devoid of any remedy and thus, are at the whims and fancy of the employer.